Meta-analysis of public health risks of lead accumulation in wastewater, irrigated soil, and crops nexus - Adane Sirage Ali; Adane Sirage Ali; Argaw Ambelu Bayih; Sirak Robele Gari (Frontiers Media S.A., 2022)
Lead (Pb) from different sources accumulate in the irrigation water, irrigated soil and in different parts of plants. Reports show contradictory findings and high variability of lead accumulation and associated public health risks. We hypothesized that lead accumulation in irrigation water, soil and edible plants is high enough to be a public health risk. By using the standard procedures for meta-analysis, 24 studies were qualified. The studies included in the meta-analysis are concentrated in few countries with strong authors' key words co-occurrence relationship. The mean concentration of Pb in the irrigation wastewater ranged from 0.0196 ± 0.01 mg/l to 52.4 ± 0.02 mg/l in wastewater and about 50% of the values are beyond the limits for irrigation water standard. The study also showed that the concentration of Pb in the irrigated soil vary significantly from a minimum of 0.04 ± 2.3 mg/l in Ethiopia to a maximum of 441 ± 19.8 mg/l in Iran (P < 0.01). Based on effect size analysis, the weight of the studies ranged from 0.1 to 5.4% indicating that the studies' contribution to the overall effect is barely different. The heterogeneity test statistics also indicates considerable variability between the studies (I2 = 98%, P-value < 0.001). The subgroup analysis showed large between-studies heterogeneity in both groups (Tau2 = 28.64; T2 = 98%). A total of 44 crops were studied, of which 38 were leafy and non-leafy vegetables. Most popular crops including spinach, cabbage and lettuce are most frequently studied crops. In all crops, the Pb level in crops produced by using untreated wastewater are beyond the WHO limit for edibility. In all of the studies, the pollution load index (PLI) and soil accumulation factor (SAF) is much higher indicating that there is a buildup of Pb concentration in wastewater irrigated soil. The plant concentration factor (PCF) calculated shows the high Pb accumulation potential of the edible parts of the crops. The health risk index (HRI) calculated shows that in all of the studied crops from India, Iraq, Morocco and Egypt are much higher than one indicating the high health risk of consumption.